2022
DOI: 10.3390/foods11182918
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Consumption Value on Consumer Willingness to Consume GM Food: A Post-COVID-19 Analysis

Abstract: In this research, we debate the critical challenges posed by the COVID-19 pandemic such as food scarcity, by examining the influence of consumption values on consumers’ willingness to consume genetically modified (GM) food in the presence of consumer food attitudes, animosity, and ethnocentrism, which could be the one possible option to deal with the food scarcity problem. The proposed relationship could help to understand the complex societal problem of food scarcity and import dependency in the food sector b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 105 publications
0
7
0
Order By: Relevance
“…For these reasons, many studies have focused on changes in consumption styles during and after the first Covid-19 global lockdown (e.g. Filimonau et al, 2022;Ghufran et al, 2022b;Bas ¸aran and Purut, 2021;Lamy et al, 2022;Chenarides et al, 2021). However, existing knowledge about the changes in food consumption over a long period of time after the pandemic event is scarce.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For these reasons, many studies have focused on changes in consumption styles during and after the first Covid-19 global lockdown (e.g. Filimonau et al, 2022;Ghufran et al, 2022b;Bas ¸aran and Purut, 2021;Lamy et al, 2022;Chenarides et al, 2021). However, existing knowledge about the changes in food consumption over a long period of time after the pandemic event is scarce.…”
Section: Discussionmentioning
confidence: 99%
“…For these reasons, many studies have focused on changes in consumption styles during and after the first Covid-19 global lockdown (e.g. Filimonau et al ., 2022; Ghufran et al ., 2022b; Başaran and Purut, 2021; Lamy et al ., 2022; Chenarides et al. , 2021).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, given the current circumstances, particularly after the COVID-19 pandemic and the political issues that have caused the economy in a country to weaken, resulting in a decrease in consumer purchasing power and inflation that has led to rising food prices, many consumers around the world suffer and find it challenging to purchase food [67]. Accordingly, GMO food is an option for consumers since it may be purchased at a lower cost [54]. As affordability is one of the most significant aspects for consumers when purchasing food products, this also makes the prospect of GMO products more appealing in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, after the COVID-19 pandemic, there has been an upsurge in the number of persons who are malnourished [54]. In addition, the economic situation has not yet completely recovered, which, along with the negative political situation between nations, has led to inflation in many nations and an increase in the price of basic foodstuffs [54]. Moreover, since the economic situation has not changed, it has become difficult for consumers to buy essential food products.…”
Section: Consumers' Knowledge Toward Genetically Modified Foodsmentioning
confidence: 99%
“…Nevertheless, some researchers reported a non-significant relationship (Awuni and Du, 2016;Joibi and Annuar, 2021). Moreover, Ghufran et al (2022) found that epistemic value leads to a positive consumer attitude. Karjaluoto et al (2019) observed that product novelty positively correlates with overall perceived value.…”
Section: Epistemic Value and Consumer Behaviormentioning
confidence: 99%